The influence of food on aging and aesthetic disorders: an integrative review (Research, Society and Development, 2021)
Growth through good shape and beauty, however, extracts the focus of the true importance for our body of adequate nutrition, showing that inadequate habits, with inadequate nutrition, have consequences for the metabolism, leading to nutritional deficiency and obesity. In a more explanatory way, ensure that the intake of nutrients happens in the right amount, so the absence of one of them can cause a metabolic imbalance, resulting in various aesthetic disorders. Studies show that aging and esthetic disorders are related to the quality of life that one leads, because, in order to have longevity, it is necessary to be aware of good eating habits. Thus, the following question was suggested as a problematization for the research project: What is influence of food on aging and the onset of aesthetic disorders? The aim of this research is to verify the influence of food on aging and aesthetic disorders through an integrative review. The methodology applied was an integrative literature research, qualitative and exploratory in nature, analyzing articles published in indexed journals dealing with the subject. As a result, 155 files were initially found that were right by selecting the search filters, according to pre-established inclusion criteria. From the preliminary filtering, 20 articles were eligible for evaluation of titles and abstracts, among these, 12 articles were excluded that were excluded for presenting repeated and book summaries and that did not satisfy the study in question. This leaves 8 articles for analysis and inclusion in this study.